Age, sex and social influences on adult survival in the cooperatively breeding Karoo Scrub-robin. (1st December 2016) - Lloyd, Penn; Martin, Thomas E.; Taylor, Andrew; Braae, Anne; Altwegg, Res
Abstract: Among cooperatively breeding species, helpers are hypothesised to increase the survival of breeders by reducing breeder workload in offspring care and increased group vigilance against predators. Furthermore, parental nepotism or other benefits of group living may provide a survival benefit to young that delay dispersal to help. We tested these hypotheses in the Karoo Scrub-robin ( Cercotrichas coryphaeus ), a long-lived, and facultative cooperatively breeding species in which male helpers make substantial contributions to the care of young. We found that annual breeder survival in the presence of helpers did not differ detectably from breeders without helpers or breeders that lost helpers. Furthermore, helpers did not gain a survival benefit from deferred breeding; apparent survival did not differ detectably between male helpers and male breeders followed from one year old. These results are consistent with other studies suggesting a lack of adult survival benefits among species where breeders do not substantially reduce workloads when helpers are present. They are also consistent with the hypothesis that males that delay dispersal make the 'best of a bad job' by helping on their natal territory to gain indirect fitness benefits when they are unable to obtain a territory vacancy nearby.